A sustainable approach for improving religious tourism in the jaffna district - Yoharajan, S. (university of Jaffna, 2014)
This research article examines a sustainable approach for improving religious tourism with a specific focus on Jaffna district. The main objective of the research paper is to examine the possibilities of community's involvement to uplift the standard of religious tourism by preserving the heritage and cultural values of the local people. Methodologically, I adopted a case study research design and privileged my participant's individual views with their voices represented in this thesis in the form of quotations. Qualitative approaches guided me to conduct fieldwork in which I held in-depth interviews, and collected notes through participating observation activities, and informal interactions in the locality. The World Tourism Organization (WTO) points out that sustainable tourism developed in certain geographical areas may become a fundamental tool in the economic development of and the reduction of poverty in certain areas. Today religious tourism is a dynamic global industry with several million travelers. They regard visiting the places of pilgrimage as their religious duty. This paper is an attempt to bring forth the rich religious and cultural heritage of the Jaffna district. It has a good blend of aspects in religious tourism in all its forms: the district has a very rich cultural heritage of architecture, art, festivals, pilgrimage sites and places of worship. Thousands of international and domestic religious tourists are visiting this area every year. This study highlight the present status of religious tourism in the Jaffna district and also point out few drawbacks which stands on the way of progress. This paper also recommends some future initiatives for betterment of this sector.
Keywords: Management committee; People's participation; Religious tourism; Sustainable approach; Tourism node